Novel clinical and molecular findings in Spanish patients with naevoid basal cell carcinoma syndrome. (22nd December 2017) - Alonso, N.; Cañueto, J.; Ciria, S.; Bueno, E.; Palacios‐Alvarez, I.; Alegre, M.; Badenas, C.; Barreiro, A.; Pena, L.; Maldonado, C.; Nespeira‐Jato, M.V.; Peña‐Penabad, C.; et al.
Summary: Background: Naevoid basal cell carcinoma syndrome (NBCCS) is an autosomal dominant disorder characterized by developmental alterations and multiple basal cell carcinomas. Mutations in PTCH1, which encodes a membrane receptor for Sonic Hedgehog, are associated with the development of the disease. Most of them produce a truncated protein, which is unable to suppress Smoothened protein and continuously activates the downstream pathway. Objectives: We aimed to characterize 22 unrelated Spanish patients with NBCCS, the largest cohort with Gorlin syndrome reported to date in Spain. Methods: Genomic analysis of PTCH1 was performed in patients with NBCCS and controls, and mutations were analysed using bioinformatics tools. Results: We report for the first time two young patients, one each with uterus didelphys and ganglioneuroma, within the context of NBCCS. One patient showing a severe phenotype of the disease had developed basal cell carcinomas since childhood. Sanger sequencing of PTCH1 in this cohort identified 17 novel truncating mutations (11 frameshift, five nonsense and one mutation affecting an exon–intron splice site) and two novel missense mutations that were predicted to be pathogenic. The patients showed great clinical variability and inconsistent genotype–phenotype correlation, as seen in relatives carrying similar mutations. Conclusions: This study contributes to increase the pool of clinical manifestations of NBCCS, as well as increasing the number of pathogenic mutations identified in PTCH1 predisposing to the condition. The inconsistencies found between phenotype and genotype suggest the involvement of other modifying factors, genetic, epigenetic or environmental. Abstract : What's already known about this topic? Naevoid basal cell carcinoma syndrome (NBCCS) is a rare autosomal dominant disorder characterized by developmental alterations and multiple basal cell carcinomas. Mutations in the PTCH1 gene are associated with the disease. Clinical manifestations are variable and inconsistent with the genotype. What does this study add? This is the largest cohort of patients with NBCCS in the Spanish population to date. We have identified 17 novel truncating mutations in PTCH1 and two novel missense mutations in these patients. We describe for the first time two patients with NBCCS with uterus didelphys and ganglioneuroma, respectively. What is the translational message? The novel clinical manifestations and PTCH1 mutations associated with NBCCS in this large series could contribute to the diagnosis of patients with unclear phenotypes. The novel PTCH1 mutations reported in this study could also contribute to improve genetic counselling for the individuals and families affected. Plain language summary available online Respond to this article